High-Resolution Characterization of Liquid-Crystalline [60]Fullerenes Using Solid-State Nuclear Magnetic Resonance Spectroscopy - Dvinskikh, Sergey V.; Yamamoto, Kazutoshi; Scanu, David; Deschenaux, Robert; Ramamoorthy, Ayyalusamy (My University, 2008)
Liq.-cryst. materials contg. fullerenes are valuable in the development of supramol. switches and in solar cell technol. In this study, we characterize the liq.-cryst. and dynamic properties of fullerene-contg. thermotropic compds. using solid-state natural abundance 13C NMR expts. under stationary and magic angle spinning sample conditions. Chem. shifts spectra were measured in isotropic, liq.-cryst. nematic and smectic A and cryst. phases using one-dimensional 13C expts., while two-dimensional sepd. local-field expts. were used to measure the 1H-13C dipolar couplings in mesophases. Chem. shift and dipolar coupling parameters were used to characterize the structure and dynamics of the liq.-cryst. dyads. NMR data of fullerene-contg. thermotropic liq. crystals are compared to that of basic mesogenic unit and mesomorphic promoter compds. Our NMR results suggest that the fullerene-ferrocene dyads form highly dynamic liq.-cryst. phases in which mols. rotate fast around the symmetry axis on the characteristic NMR time scale of ?10-4 s. [on SciFinder(R)]
Keywords: fullerene deriv liq crystal NMR